The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jafc.0c01778
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Lipidomics Analysis Reveals the Antiobesity and Cholesterol-Lowering Effects of Tangeretin in High-Fat Diet-Fed Rats

Abstract: Tangeretin (TAN) exhibited antilipogenic, antidiabetic, and lipid-lowering effects. However, the lipid biomarkers and the underlying mechanisms for antiobesity and cholesterol-lowering effects of TAN have not been sufficiently investigated. Herein, we integrated biochemical analysis with lipidomics to elucidate its efficacy and mechanisms in high-fat diet-fed rats. TAN at supplementation levels of 0.04 and 0.08% not only significantly decreased body weight gain, serum total cholesterol, and low-density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 47 publications
5
37
0
Order By: Relevance
“…TAN ingested as 0.04, and 0.08 percent of the HFD for 6 weeks significantly lowered body weight gains. The lower body weights were mainly attributable to decreased adipose tissue produced with supplementation with TAN (Feng et al., 2020). In these HFD‐fed rats, the antiobesity and cholesterol‐lowering effects of TAN were linked to the ability of TAN to modulate hepatic lipid biosynthesis, particularly shown by sharply lowered levels of serum triglycerides and total‐C.…”
Section: Discussionmentioning
confidence: 99%
“…TAN ingested as 0.04, and 0.08 percent of the HFD for 6 weeks significantly lowered body weight gains. The lower body weights were mainly attributable to decreased adipose tissue produced with supplementation with TAN (Feng et al., 2020). In these HFD‐fed rats, the antiobesity and cholesterol‐lowering effects of TAN were linked to the ability of TAN to modulate hepatic lipid biosynthesis, particularly shown by sharply lowered levels of serum triglycerides and total‐C.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the negative feedback regulation of bile acid synthesis, interactions with plant compounds may cause an increase in the conversion of cholesterol to primary bile acids. Accordingly, activations of CYP7A1, the rate-limiting enzyme of bile acid synthesis, were described after diet interventions with plant compounds such as highly viscous apple pectin [114] or tangeretin, a flavonoid derived from citrus peel [115]. These studies indicate that the viscosity-related or molecular interactions described for these plant compounds may contribute to lowering blood cholesterol levels.…”
Section: Bile Acid Interactions and Influences On Healthmentioning
confidence: 99%
“…This is important because NOB and TAN are very bitter compounds [25]. Feng et al [26] suggested an anti-obesity effect of TAN due to lower weight gain and body fat in rats that consumed 0.04% and 0.08% TAN mixed with a high-fat diet. Compared to the current experiment, these doses were 4.6 to 9.1 times higher, the initial body weight was 50% higher and, the intervention was longer (6 wk).…”
Section: Discussionmentioning
confidence: 99%